Impact of digital twins on the economic efficiency of quality management of metal products in industrial mechanical engineering - Kolosov, Artem (Академічні візії, 2026)
The relevance of the study is determined by the growing requirements for the quality of metal products under increasingly complex production conditions and the need to improve the economic efficiency of management in industrial mechanical engineering. Traditional quality control approaches do not ensure sufficient proactivity and economic justification of decisions, which necessitates the application of digital technologies. The aim of the study is to examine the impact of digital twins on the economic efficiency of quality management of metal products in industrial mechanical engineering and to substantiate directions for improving the effectiveness of managerial decisions. Methods. The research employs methods of system analysis, generalization, structural-functional approach, and logical-analytical modeling. Results. The economic essence and functional capabilities of digital twins in the quality management system have been investigated. The mechanisms of their influence on the formation of economic results of production have been identified, including adaptive process control, prediction of deviations, and integration of analytical tools into decision-making. Approaches to integrating digital twins into quality control and assurance processes have been generalized, ensuring a transition to end-to-end quality management. It has been proven that the economic effect is formed through the coordination of “cost – time – quality” parameters within a unified digital environment. The main scientific and practical problems of evaluating efficiency have been identified, including the lack of unified methodologies, the difficulty of quantifying indirect effects, and the dependence on data quality. Conclusions. Practical recommendations for improving the economic efficiency of quality management based on the phased implementation of digital twins, their integration into planning systems, and the establishment of feedback loops have been substantiated. It has been established that their application contributes to cost reduction, defect minimization, and improved stability of product quality. Prospects for further research are associated with the development of quantitative models for evaluating the economic efficiency of digital twins, the formation of integrated “quality–economics” indicators, and the study of scaling mechanisms for digital solutions in complex production systems.